Seed Maturation and Hard Seed Development in Crotalaria (Crotalaria juncia) - M. KHANNA,; A.K. VARI,; S. BARANWAL,; S.P. SHARMA,; I. JETHANI, (Seed Research, 2026)
Field experiments were conducted during Kharif 2002 and 2003 to study seed quality in relation to seed development and maturity in four genotypes of Crotalaria. The results indicated differences among genotypes in number of days to initiation of flowering and duration of seed maturation. Physiological maturity was attained between 40-50 DAA and at this stage the seeds had maximum germination, vigour and viability. Field maturity was attained at 50-70 DAA, depending upon genotypes and was also influenced by the temperature and humidity prevailed during seed maturation and development. Development of physical seed dormancy (hard seeds) due to impermeable seed coat was found to be closely associated with weather conditions during later stages of seed maturation. Maximum number of hard seeds was observed in the year 2002 probably due to drought like conditions causing a sudden drop in seed moisture at physiological maturity, while in 2003 comparatively milder temperature and higher R.H. prolonged seed maturation process and significantly decreased the hard seed development.